Different roles of alpha and beta band oscillations in anticipatory sensorimotor gating - Buchholz, Verena N.; Jensen, Ole; Medendorp, W. Pieter (Frontiers in Human Neuroscience, 2014)
Alpha (8-12Hz) and beta band (18-30Hz) oscillations have been implicated in sensory anticipation and motor preparation. Here, using magneto-encephalography, we tested whether they have distinct functional roles in a saccade task that induces a remapping between sensory and motor reference frames. With a crossed hands posture, subjects had to saccade as fast and accurate as possible toward a tactile stimulus delivered to one of two non-visible index fingers, located to the left or right of gaze. Previous studies have shown that this task, in which the somatotopic stimulus must be remapped to activate oculomotor system in the opposing hemisphere, is occasionally preceded by intrahemispheric remapping, driving a premature saccade into the wrong direction. To test whether the brain could anticipate the remapping, we provided auditory predictive cues (80% validity), which indicated which finger is most likely to be stimulated. Both frequency bands showed different lateralization profiles at central versus posterior sensors, indicating anticipation of somatosensory and oculomotor processing. Furthermore, beta band power in somatosensory cortex correlated positively with saccade reaction time (SRT), with correlation values that were significantly higher with contralateral versus ipsilateral activation. In contrast, alpha band power in parietal cortex correlated negatively with SRT, with correlation values that were significantly more negative with ipsilateral than contralateral activation. These results suggest distinct functional roles of beta and alpha band activity: 1) somatosensory gating by beta oscillations, increasing excitability in contralateral somatosensory cortex (positive correlation) and 2) oculomotor gating by posterior alpha oscillations, inhibiting gaze-centered oculomotor regions involved in generating the saccade to the wrong direction (negative correlation). Our results show that low frequency rhythms gate upcoming sensorimotor transformations.